Transformasi Pendidikan di Era Kecerdasan Buatan: Tinjauan Literatur tentang Integrasi Artificial intelligence dalam Pembelajaran Abad ke-21 - Taher Subagja; Arjuna Dwi Laksita; Ahmad Darmawan (CV. Global Cendekia Inti, 2026)
The digital transformation of education has accelerated significantly alongside the rapid advancement of Artificial Intelligence (AI) as a catalyst for 21st-century pedagogical change. AI is no longer positioned merely as a technological tool; rather, it represents a new paradigm that enables adaptive learning, data-driven personalization, and automated feedback within digital education ecosystems. This article conducts a narrative–systematic literature review of 25 indexed journal articles published between 2023 and 2026 to comprehensively map AI-driven educational transformation. The analysis focuses on trends in AI integration, its impact on learning outcomes, its contribution to strengthening 21st-century skills, and its pedagogical and ethical implications. The findings indicate that AI implementation—particularly through intelligent tutoring systems, adaptive learning, and AI-based feedback—contributes to improved learning outcomes, enhanced critical thinking, creativity, and student engagement. However, this transformation also raises challenges related to algorithmic bias, data privacy, and disparities in AI literacy. The study proposes a conceptual model of AI-based educational transformation emphasizing the integration of digital infrastructure, AI-based pedagogy, personalized learning, 21st-century competencies, and ethical governance.